1918
DOI: 10.1001/jama.1918.02600070001001
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Lipovaccines

Abstract: The advances that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1918
1918
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…More recently Colonel Whitmore has substituted cottonseed oil containing 2 per cent lanolin for olive oil, as it appears to be less irritating to the subcutaneous tissue. Whitmore, Fennel, and Petersen (2) found that the triple typhoid vaccine in oil produced even better agglutination response in the serum than the same vaccine in saline solution. The reaction, both local and general, following the injection of the typhoid lipovaccine was so mild that the three original doses of saline vaccine could be combined into one dose (1 cc.)…”
Section: II and I I I Pneumococci Is Practical And That It Affords Smentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Colonel Whitmore has substituted cottonseed oil containing 2 per cent lanolin for olive oil, as it appears to be less irritating to the subcutaneous tissue. Whitmore, Fennel, and Petersen (2) found that the triple typhoid vaccine in oil produced even better agglutination response in the serum than the same vaccine in saline solution. The reaction, both local and general, following the injection of the typhoid lipovaccine was so mild that the three original doses of saline vaccine could be combined into one dose (1 cc.)…”
Section: II and I I I Pneumococci Is Practical And That It Affords Smentioning
confidence: 99%
“…These infiltrations were never serious, but caused some anxiety and discomfort to the patient. It was a fortunate coincidence, therefore, that just at this time Colonel Eugene R. Whitmore (2), of the Medical Corps, U. S. Army, made his first report on the use of vegetable oil as a vehicle for the suspension of bacterial vaccines. Some work had already been done along, this line in France by Le Moignic and Pinoy (3) who had tried suspending triple typhoid vaccine in vegetable oils, and had met with promising results.…”
Section: II and I I I Pneumococci Is Practical And That It Affords Smentioning
confidence: 99%
“…2 Earlier OMV vaccines were detoxified chemically, an approach Whitmore took with whole cell vaccines in 1918. 5 While this approach does decrease the endotoxic activity of the OMV, it also removes most of the antigenic lipoproteins in the outer membrane, many of which are highly conserved among case strains of group B meningococcus and may be essential to induce a broadly protective immune response. It is hoped that NOMV vaccines will retain these conserved minor antigens and that the altered LOS will have enough pro-inflammatory activity to serve as an immune-enhancing adjuvant.…”
mentioning
confidence: 99%